Municipal solid waste management: Integrated analysis of environmental and economic indicators based on life cycle assessment - Paes, Michel Xocaira [UNESP]; Medeiros, Gerson Araujo de [UNESP]; Mancini, Sandro Donnnini [UNESP]; Bortoleto, Ana Paula; Puppim de Oliveira, Jose A.; Kulay, Luiz Alexandre (Elsevier B.V., 2020)
This paper develops a method to analyze municipal solid waste management systems (MSWMS) that integrates environmental and economic indicators using Life Cycle Assessment (LCA) and Life Cycle Costing (LCC). The method was tested in the city of Sorocaba, Brazil, a medium size municipality typical of many developing countries. Environmental impacts were analyzed considering system expansion, which combined the aspects of primary production and recycling processes with the impacts of MSWMS. The economic analysis included operating and investment costs to the costs of environmental externalities, thus enabling the analysis of total costs to society. An integrated analysis of environmental indicators revealed that the most significant reductions in environmental impacts occurred in the scenarios with higher rates of reuse of dry waste through recycling (70%), which lowered these impacts by up to 50% when compared to the current scenario. An analysis of economic performance indicated that the two scenarios that combined the highest recycling goals with greater transport efficiency and more composting yielded the best results, reducing the total social costs by 31% and 33%, respectively. Lastly, the integration of environmental and economic analyses revealed that the best results are obtained by a combination of composting, mechanical biological treatment and recycling, which would reduce the impacts of MSWMS by up to 33.7 points per invested dollar. The results supports the application of this proposed integrate approach to improve the current solid waste management system in Sorocaba and in other cities with a similar system and waste generation. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Environmental life cycle assessment; Life cycle costing; Environmental and economic performance indicators; Municipal solid waste management; Public policy